Cerebellar disorders : a practical approach to diagnosis and management - Manto, Mario; Cambridge eBooks (Cambridge : Cambridge University Press, 2010)
During the last three decades, many laboratories worldwide have dedicated their research activities to understanding the roles of the cerebellum in motor control, cognitive processes and the biology of mental processes, behavioral symptoms and emotion. These advances have been associated with discoveries of new clinical disorders, in particular in the field of genetic ataxias, and the growing number of diseases presents a source of difficulty for clinicians during daily practice. This practical guide summarizes and evaluates current knowledge in the field of cerebellar disorders. Encompassing details of both common and uncommon cerebellar ataxias, including vascular, immune, neoplastic, infectious, traumatic, toxic and inherited disorders, this book will assist clinicians in the diagnosis and management of the full spectrum of cerebellar ataxias encountered in daily practice. Essential reading for clinicians, including general practitioners, neurologists, pediatricians, radiologists, psychiatrists and neuropsychologists, this will also prove a valuable tool for students, trainees and researchers.
Embryology and anatomy -- Physiology of the cerebellum -- Symptoms of cerebellar disorders -- Clinical scales -- Diagnosis of cerebellar disorders as a function of age -- Overview of the general management of cerebellar disorders -- Malformations -- Cerebellar stroke -- Immune diseases -- Endocrine disorders -- Infectious diseases -- Corticobasal degeneration -- Tumors and paraneoplastic disorders -- Trauma of the posterior fossa -- Toxic agents -- Austism spectrum disorders and ataxia -- Progressive myoclonic epilepsies -- Multiple system atrophy -- Essential tremor -- Autosomal recessive cerebellar ataxias -- Mitochondrial disorders -- X-link?ed ataxias -- Dominant ataxias.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Cerebellum -- Diseases; Electronic books